Genotypic Diversity of Escherichia coli in the Water and Soil of Tropical Watersheds in Hawaii - Goto, Dustin K. (American Society for Microbiology, 2011)

(untitled)
High levels of Escherichia coli were frequently detected in tropical soils in Hawaii, which present important environmental sources of E. coli to water bodies. This study systematically examined E. coli isolates from water and soil of several watersheds in Hawaii and observed high overall genotypic diversity (35.5% unique genotypes). In the Manoa watershed, fewer than 9.3% of the observed E. coli genotypes in water and 6.6% in soil were shared between different sampling sites, suggesting the lack of dominant fecal sources in the watershed. High temporal variability of E. coli genotypes in soil was also observed, which suggests a dynamic E. coli population corresponding with the frequently observed high concentrations in tropical soils. When E. coli genotypes detected from the same sampling events were compared, limited sharing between the soil and water samples was observed in the majority of comparisons (73.5%). However, several comparisons reported up to 33.3% overlap of E. coli genotypes between soil and water, illustrating the potential for soil-water interactions under favorable environmental conditions. In addition, genotype accumulation curves for E. coli from water and soil indicated that the sampling efforts in the Manoa watershed could not exhaust the overall genotypic diversity. Comparisons of E. coli genotypes from other watersheds on Oahu, Hawaii, identified no apparent grouping according to sampling locations. The results of the present study demonstrate the complexity of using E. coli as a fecal indicator bacterium in tropical watersheds and highlight the need to differentiate environmental sources of E. coli from fecal sources in water quality monitoring.